Computation Application: Techno-Economic Analysis on the Production of Magnesium Oxide Nanoparticles by Precipitation Method - Lidia Intan Febriani; Citra Nurhashiva; Jessica Veronica; Risti Ragadhita; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2020)
This study aims to analyze the feasibility of a project for the production of magnesium oxide nanoparticles using precipitation methods on a large scale. The feasibility analysis of this project was determined using an evaluation from an economic and engineering perspective. Evaluation from an engineering perspective is determined by the evaluation of the initial factory design and stoichiometric calculations. Meanwhile, the evaluation from an economic perspective is determined by several parameters, such as Payback Period, Gross Profit Margin, Cumulative Net Present Value, etc. The analysis results show that the production of magnesium oxide nanoparticles using the precipitation method can be carried out on an industrial scale. In this project, 11,250 kg of magnesium oxide nanoparticles were obtained per day, and the total profit earned was 1,881,184,752.91 USD in 10 years. Payback Period analysis shows that the investment will be profitable after more than three years. To ensure project feasibility, projects are estimated from ideal to worst-case conditions in production, including salary, sales, raw materials, utilities, and external conditions such as taxes.